Oncolytic herpes simplex viruses for the treatment of glioma and targeting glioblastoma stem-like cells - Kardani, Kimia; Sanchez Gil, Judit; Rabkin, Samuel D. (Frontiers in Cellular and Infection Microbiology, 2023)
Glioblastoma (GBM) is one of the most lethal cancers, having a poor prognosis and a median survival of only about 15 months with standard treatment (surgery, radiation, and chemotherapy), which has not been significantly extended in decades. GBM demonstrates remarkable cellular heterogeneity, with glioblastoma stem-like cells (GSCs) at the apex. GSCs are a subpopulation of GBM cells that possess the ability to self-renew, differentiate, initiate tumor formation, and manipulate the tumor microenvironment (TME). GSCs are no longer considered a static population of cells with specific markers but are quite flexible phenotypically and in driving tumor heterogeneity and therapeutic resistance. In light of these features, they are a critical target for successful GBM therapy. Oncolytic viruses, in particular oncolytic herpes simplex viruses (oHSVs), have many attributes for therapy and are promising agents to target GSCs. oHSVs are genetically-engineered to selectively replicate in and kill cancer cells, including GSCs, but not normal cells. Moreover, oHSV can induce anti-tumor immune responses and synergize with other therapies, such as chemotherapy, DNA repair inhibitors, and immune checkpoint inhibitors, to potentiate treatment effects and reduce GSC populations that are partly responsible for chemo- and radio-resistance. Herein, we present an overview of GSCs, activity of different oHSVs, clinical trial results, and combination strategies to enhance efficacy, including therapeutic arming of oHSV. Throughout, the therapeutic focus will be on GSCs and studies specifically targeting these cells. Recent clinical trials and approval of oHSV G47Δ in Japan for patients with recurrent glioma demonstrate the efficacy and promise of oHSV therapy.